Physicochemical characteristics of oil-based cuttings from pretreatment in shale gas well sites. Issue 9 (28th July 2020) - Jiang, Guobin; Yu, Jinlei; Jiang, Huashan; Xu, Bo; Tang, Pan; Zhao, Liang; Li, Hui; Xiang, Qigui; Hu, Jinyan
Abstract: Understanding the physicochemical characteristics of oil-based cuttings (OBCs) is an important foundation for subsequent treatment and management. The macro- and microscopic properties of white oil-based cuttings (WOBCs) and diesel-based cuttings (DBCs) after the different pretreatment steps have been assessed using scanning electron microscopy. The organic and inorganic compositions of OBCs have been analyzed using X-ray diffraction, Fourier-transform infrared spectrometry, and gas chromatography–mass spectrometry. Inorganic matter (SiO2, BaSO4, and CaCO3 ), alkanes, aromatic compounds, and water were the main components of OBCs. The organic content (26.14%) and alkane content of the WOBCs were higher than that of the DBCs, whereas for the inorganic content (70.87%), the reverse was true. The macro- and micromorphologies of OBCs were quite different because their oil and water contents were different. The oil contents of OBCs decreased in the order A1 (14.64%) > A3 (12.67%) > A2 (11.06%) and B1 (9.19%) > B3 (8.94%) > B2 (4.66%); the water contents decreased in the order A1 (2.99%) > A3 (2.19%) > A2 (1.09%) and B1 (2.30%) > B3 (1.87%) > B2 (1.09%). Moreover, a skid-mounted treatment technology for OBCs was proposed. The results can be a scientific guidance for the treatment and management of OBCs.